294 BEYOND BRUGADA SYNDROME: A COMMON ECG PATTERN IN AN UNCOMMON CLINICAL SCENARIO. (15th December 2022) - Coretti, Francesca; Brugiatelli, Leonardo; Sfredda, Sara; Coraducci, Francesca; Torselletti, Lorenzo; Belleggia, Sara; Paolini, Federico; Alfieri, Michele; Bastianoni, Gianmarco; Principi, Samuele; Ciliberti, Giuseppe; Barbarossa, Alessandro; et al.
Abstract: Propofol infusion syndrome (PRIS) is a rare but potentially lethal side effect of propofol. In most cases it shows various combinations of signs such as unexplained metabolic acidosis, rhabdomyolysis, hepatomegaly, renal failure, hypertriglyceridemia, malignant arrhythmia and rapidly progressive cardiac failure. The development of coved ST elevation in the right precordial leads of the electrocardiogram (ECG), similar to that seen in the type I Brugada syndrome may be the first sign of cardiac instability. There is no specific treatment for PRIS. Successful management consists of an early recognition of its signs followed by a prompt propofol infusion termination. We present the case of a 35-year-old male affected by mild hypertension. He was found by his wife during a transitory loss of consciousness episode. He had resulted positive to Sars Cov 2 infection a day before and was symptomatic for fever and myalgia. An ambulance was immediately called and the patient was transferred to the emergency department for a suspected out-of-hospital-cardiac arrest. The initial one-lead ECG performed by the emergency physician was unremarkable. On arrival he was in a coma state but with stable hemodynamics. ECG showed only an asymmetric T wave inversion in V4-V6 leads. The cardiac echocardiogram did not show any major alterations. In the meantime, due to worsening of respiratory function, orotracheal intubation was performed and the patient was sedated with propofol, midazolam and fentanyl. Subsequently, an episode of atrial fibrillation was documented. Amiodarone infusion was started and the patient reverted to sinus rhythm after a few hours. The following day two episodes of Torsade de Pointes during prolonged QTc (660 ms) occurred. These arrhythmias were treated successfully with magnesium sulfate infusion. Blood analysis showed severe hypokalemia that was immediately corrected. After the hemodynamic stabilization the ECG showed a pattern highly resembling the Brugada pattern type 1 in the right precordial leads. Moreover CPK, myoglobin, high sensitivity troponin I levels started to rise, along with creatinine, triglycerides and markers of hepatic injury. Propofol had been administered continuously for eight days, so PRIS was suspected as the primum movens of this clinical scenario. Propofol infusion was immediately interrupted. Thereafter, the patient gradually improved and was extubated. As soon as the patient's hemodynamic conditions allowed it, a coronary CT and a cardiac MRI were performed, but were unremarkable. To further evaluate the case, a flecainide challenge test was performed, but no significant ECG change was induced. Nonetheless, given both the history of ventricular arrhythmia, the young age of the patient and the unexplained transitory loss of consciousness a subcutaneous defibrillator was implanted as a form of secondary prevention.